Comprehensive clinical, radiological, pathological and biochemical analysis required to differentiate VV1 sporadic Creutzfeldt-Jakob disease from suspected variant CJD. Issue 1 (19th April 2022) - Holper, Sarah; Lewis, Victoria; Wesselingh, Robb; Gaillard, Frank; Collins, Steven J; Butzkueven, Helmut
Abstract : Background: A diagnosis of variant Creutzfeldt-Jakob disease (vCJD), the zoonotic prion disease related to transmission of bovine spongiform encephalopathy, can carry enormous public health ramifications. Until recently, all vCJD clinical cases were confined to patients displaying methionine homozygosity (MM) at codon 129 of the prion protein gene ( PRNP ). The recent diagnosis of vCJD in a patient heterozygous (MV) at codon 129 reignited concerns regarding a second wave of vCJD cases, with the possibility of phenotypic divergence from MM vCJD and greater overlap with sporadic CJD (sCJD) molecular subtypes. Method and results: We present a case of CJD with clinico-epidemiological and radiological characteristics creating initial concerns for vCJD. Thorough case evaluation, including data provided by genetic testing, autopsy and neuropathological histological analyses, provided a definitive diagnosis of the rare VV1 molecular subtype of sCJD. Conclusion: Distinguishing vCJD from sCJD is of vital public health importance and potentially more problematic with the development of non-MM vCJD cases. The patient described herein demonstrates that in addition to the clinico-epidemiological profile, combined supplementary pathological, biochemical and critical radiological analysis may be necessary for confident discrimination of sCJD, especially rare sub-types, from vCJD.